Introduction - Editors (Revista do Colóquio, 2026)
Issue No. 27 of Revista do Colóquio brings together research and creative work presenting diverse modes of inquiry into art, culture, language, memory, the city, and creative processes. The texts in this volume highlight the variety of approaches within the field of the arts, bridging historical analyses, theoretical reflections, studies of contemporary practices, mediation experiences, and visual essays. We have gathered contributions stemming from distinct subjects and contexts, yet sharing a common interest in understanding how artistic practices forge relationships with their spaces of circulation, their audiences, and their symbolic repertoires.
Keywords: introduction; edition; arts journal